INVESTIGATION OF SPORTS SCIENCES STUDENTS’ ECONOMI LITERACY AND FREQUENCY OF FOLLOWING THE ECONOMY ACCORDING TO DEMOGRAPHIC VARIABLES (Third Sector Social Economic Review, 2025)
The aim of this research is to examine whether the economic literacy and frequency of following the economy of the students of the Faculty of Sports Sciences differ in terms of some demographic characteristics. The research is a quantitative research model and was conducted with the relational screening method. The universe of the research consists of approximately 650 students studying at the undergraduate level at the Faculty of Sports Sciences of Iğdır University. The sample of the research consists of a total of 246 students, 147 of whom are male (Xage= 23.36±.430) and 99 of whom are female (Xage= 22.03±.386), studying in three different education programs within the Faculty of Sports Sciences. Data were collected through an online survey. Since the normality condition was provided, Chi-Square test, Independent Samples t-test and One-Way Variance (ANOVA) Test from the parametric tests were applied in testing the hypotheses of the research and making comparisons. As a result of the research, it was determined that there was a significant difference between the gender, age, personal income, curiosity about economic events and having taken an economics course of sports sciences students and their frequency of following the economy and economic literacy knowledge. The results suggested that students should be able to raise their incomes by alternative means, provide educational and educational services to women students in terms of economic literacy, ensure that they receive daily notifications on their smartphones by setting up programmes related to economics literacy and more practices for students under the age of 25.
Keywords: Economics; Literacy; Sports science students; Economic literacy; University